Current strategies for the management of oral mucositis induced by radiotherapy or chemotherapy - Trucci, Victoria Martina (2009)
Oral mucositis is a clinically relevant complication during the treatment of cancer patients. It is frequently seen in subjects receiving high doses of radiation therapy in the head-neck region, chemotherapy or a combination of these treatment modalities. Due to its complex pathophysiology, this type of inflammation can also affect the gastrointestinal tract, which has attracted the attention of medical professionals. The oncologic treatment does not distinguish the malignant cells from the normal epithelial cells of the mucosa because of their high-proliferative capacity. Thus, the mucosa becomes atrophic and more susceptible to trauma, allowing the development of inflammation and installation of secondary infections, which aggravates the patient clinical conditions and reduces the quality of life. The clinical management of mucositis includes preventive and palliative strategies. The preventive measures are the education and monitoring of patients in relation to their oral hygiene. The palliative measures should be adopted as early as the mucosa lesions occur and involve the use of oral solutions, topical anesthetics, analgesics and anti-inflammatory agents, lasertherapy, cryotherapy, and other clinical alternatives to control mucositis and provide comfort to the patient.